Chemoimmunotherapy for advanced gastrointestinal carcinomas: A successful combination of gene therapy and cyclophosphamide - Malvicini, Mariana (2012)
The combination of a single low dose of cyclophosphamide (Cy) with the adenovirus-mediated gene transfer of interleukin-12 (AdIL-12) might represent a successful therapy for experimental gastrointestinal tumors. This approach has been proven to revert immunosuppressive mechanisms elicited by cancer cells and to synergistically promote antitumor immunity. In addition, this therapeutic regimen has been shown to be more efficient in achieving complete tumor regressions in mice than the application of a metronomic schedule of Cy plus AdIL-12.